Perception and Motivation of National Health Insurance Program Participation in Bogor - Fika Hardini Lestari; Mohamad Djemdjem Djamaludin (Journal of Consumer Sciences, 2017)
The objective of the study was to analyze the perceptions and motivation of National Health Insurance Program (NHIP) in Bogor. This research design was cross sectional study with 140 respondents by non probability sampling method with convienience & accidental sampling technique. Data were collected by questionnaires filled out directly by the participants. The perception of NHIP participants were in the moderate category and the perception of the respondents which was not the participants of NHIP was in the bad category. Motivation of NHIP was in middle category while the respondents were not a NHIP and the motivation was categorized low. The test results showed that the age, perception and motivation had a significant positive relationship. The results showed that the perception and motivation had a very significantly positive effect on the participation of National Health Insurance Program.